2020
DOI: 10.3390/diagnostics10050332
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Parkinson’s Disease by A Metabolomics-Based Laboratory-Developed Test (LDT)

Abstract: A laboratory-developed test (LDT) is a type of in vitro diagnostic test that is designed, manufactured and used in the same laboratory (i.e., an in-house test). In this study, a metabolomics-based LDT was developed. This test involves a blood plasma preparation, direct-infusion mass spectrometry analysis with a high-resolution mass spectrometer, alignment and normalization of mass peaks using original algorithms, metabolite annotation by a biochemical context-driven algorithm, detection of overrepresented meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…The selection of PD to test this LDT was not an accident. Previously, it has been shown that an LDT can reveal the pathway overrepresentation efficient for the diagnosis of PD [ 12 ], thus making it reasonable to complete LDT development by introducing metabolic data about diseases, different organism conditions, and metabolite location. Figure 3 shows the representation scores for each participant in this study and each metabolite set.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The selection of PD to test this LDT was not an accident. Previously, it has been shown that an LDT can reveal the pathway overrepresentation efficient for the diagnosis of PD [ 12 ], thus making it reasonable to complete LDT development by introducing metabolic data about diseases, different organism conditions, and metabolite location. Figure 3 shows the representation scores for each participant in this study and each metabolite set.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the application of this algorithm for blood plasma samples have been described previously [ 17 ]. The next release of this algorithm with updated source code to make it more suitable for blood samples was recently used in the LDT [ 12 ] and applied in this work.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several LDTs have been published for the diagnosis of various diseases, including genetic disorders, cancer, infections, and other disorders [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Among them, research papers on metabolomics have been published that describe the early diagnosis of Parkinson’s disease [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%